A Study of Post-Demonetization Effect As Reflected in Novel Innovative Trend in Indian Scenario: Exploring the Impact of Demonetization on Innovative Trends in the Indian Economy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The government-endorsed numerous incentives to encourage individuals for the use of innovative practices post demonetization in India. One of the measures engaged due to demonetization was the advancement of innovative technology-based transactions. There are several facilitators which have paved the way to the development of digital payment mechanism and the occurrence of the change from the cash economy to a less-cash economy. On November 8, 2016, Prime Minister Narendra Modi proclaimed demonetization of Rs. 500 and Rs. 1,000 currency notes. In 2016 India demonetization happened in India but it took place before also in India. As in India before 2016 demonetization happened before also. In 1946, RBI (reserve bank of India) made demonetization of Rs. 1,000 and Rs. 10,000 currency notes which were then under circulation. In 1954, the government instituted currency notes of Rs. 1,000, Rs. 5,000, and Rs. 10,000. In 1978, the Moraji Desai government demonetized Rs. 1,000, Rs. 5,000, and Rs. 10,000 to limit unlawful transactions.